2017
DOI: 10.7163/gpol.0076
|View full text |Cite
|
Sign up to set email alerts
|

Cloud cover over Spitsbergen and its relation to atmospheric circulation (1983-2015)

Abstract: This paper discusses the cloud cover and its relation to atmospheric circulation over Spitsbergen during 1983Spitsbergen during -2015. It focuses on monthly and seasonal cloud covers and on the frequency of days with specific cloud cover (cloudless, clear, cloudy and completely overcast sky) and their relation to various circulation types. In the research period the cloud cover characteristics were differentiated over the island on both monthly and seasonal scales, and they strongly depended on the direction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…They found that the highest mean diurnal C occurs with air mass advection from southern directions (for types S + SWa and S + SWc). These dependencies have been confirmed by Lipiński and Łupikasza (2016) and Łupikasza and Lipiński (2017) for three Spitsbergen stations (Ny-Ålesund, Svalbard Lufthavn and Hornsund). They also found that C on Spitsbergen is greatest for southerly advection types, regardless of baric regime (S + SWc and S + SWa).…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…They found that the highest mean diurnal C occurs with air mass advection from southern directions (for types S + SWa and S + SWc). These dependencies have been confirmed by Lipiński and Łupikasza (2016) and Łupikasza and Lipiński (2017) for three Spitsbergen stations (Ny-Ålesund, Svalbard Lufthavn and Hornsund). They also found that C on Spitsbergen is greatest for southerly advection types, regardless of baric regime (S + SWc and S + SWa).…”
Section: Discussionsupporting
confidence: 54%
“…They also found that C on Spitsbergen is greatest for southerly advection types, regardless of baric regime (S + SWc and S + SWa). By far the lowest C was associated with N + NEa and N + NEc types (Łupikasza and Lipiński 2017). On Kaffiøyra, too, C was highest during air inflow from the S-W sector, under both anticyclonic and cyclonic regimes.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Afterwards, a circulation type classification (as the one developed by Belleflamme et al [67]) could be used to associate the daily cloudiness to some types of general circulation. The temporal evolution of these circulation types could then be studied as was done in Bednorz et al [68] and Lupikaszca and Lipinski [69]. Finally, it might also be interesting to verify whether such a decrease in cloudiness would be projected if MAR was forced by GCM-based future projections.…”
Section: Discussionmentioning
confidence: 99%
“…Svalbard is a mountainous, heavily glacierized archipelago in the high‐Arctic (Figure a). The main characteristics of the regional climate are: (a) relatively mild air temperatures for the latitude (77°–80°N) due to the proximity of the warm West Spitsbergen Current (Førland et al , ; Walczowski and Piechura, ); (b) frequent coreless winters, mid‐winter warm‐spells, thawing events and large day‐to‐day winter temperature variability (Bednorz and Fortuniak, ); (c) high relative humidity, cloudiness and wind speeds (Esau and Repina, ; Maturilli et al , ; Łupikasza and Lipiński, ); (d) relatively low precipitation (200–600 mm) (Førland et al , ); (e) strong seasonal contrasts in global radiation (polar night and midnight‐sun) (Maturilli et al , ); and (f) high weather sensitivity to changes in atmospheric circulation and sea ice conditions (Isaksen et al , ). Additionally, the local climate is significantly influenced by distance to the surrounding seas, relief and surface characteristics (e.g., Bednorz and Kolendowicz, ; Przybylak et al , ; Gjelten et al , ; Araźny et al , ).…”
Section: Study Areamentioning
confidence: 99%